Pengembangan Sistem Manajemen Seminar Interaktif Berbasis Web (Studi Kasus: Universitas Brawijaya Televisi) - Ananda Putra Alfa Robby; Achmad Arwan; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In organizing academic activities, University of Brawijaya Television has many agendas to hold seminars and socialization about the process of completion of work and the process of delivery of related sciences. The number of seminar schedules at UBTV makes its leaders unable to see how far the progress of seminar submissions is processed. Then in the implementation of the seminar, the number of participants or speakers who have high degrees and positions makes the seminar participants ashamed to ask if they do not have a high level of confidence. The lack of time in the question and answer session became a problem for participants to ask questions, so there were participants that were still wondering since their questions are not answered yet. This has an effect on the knowledge of the participants if they do not know the answers to the questions that want to be asked during the seminar and socialization. Based on these problems, this study proposed an interactive seminar management system based on the web that is expected, with the system, participants can ask anything they don't understand about the seminar without any embarrassment. Besides, they also can manage the time of the seminars and socialization in this institution. This system is designed along with Object-Oriented method implemented with Laravel framework in PHP programming language as well as MySQL database. The tryout is done with the approach of black box and white box to get a valid results so that it can be concluded that the system works according to the needs and solve user problems.